Prescribing Practices of Antibiotics in ARI Under the Age of Five and Factors Influencing Prescribing Antibiotics - K, Khalid; H, Ahmadullah; J, Iqbal; AA, Salam; A, Waqar (Indian Journal of Pharmacy Practice)
Background & Objective: This study was conducted to describe and obtain the baseline data about the irrational use of antibiotics in children under the age of five with Acute Respiratory Infection (ARI). Methodology: Across sectional study was conducted in about 25 general and pediatric clinics in Karachi, Pakistan. A total of 500 prescriptions were collected and analyzed using quantitative technique. Results: Overall results revealed that 100% of patients of ARI were treated with antibiotics by Consultants and General practitioners. It confirms that the quality of prescribing antibacterial agents in ARI in children is inadequate. The major classes of antibiotics used were Penicillin 24%, Macrolide 32%, Second Generation Cephalosporins 20%, and Third Generation Cephalosporins 24%. Regarding qualification of Prescribers MBBS, Consultants and Paramedics were 70%, 10%, and 20% respectively. The study also reflects the immediate urgency to develop an independent mechanism for practitioners to ensure that the patient gets proper evidence-based treatment. Conclusion: This study indicates irrational prescribing practices in ARIs in children under the age of five, so there is an immediate need of educational intervention along with several follow ups, in collaboration with national and international health care organizations in order to improve the practice to be rational especially using antibiotic in children under age of 5 years, which some time cause untoward effects and these toxic effects would be incurable especially in ARI.
Keywords: Irrational drug use; Antibiotics; Children; Cross-sectional Study